The Impact of Barrier Layers on Arabian Sea Surface Temperature Variability. Issue 3 (10th February 2020) - Echols, Rosalind; Riser, Stephen C.
Abstract: Barrier layers (BLs) in the Arabian Sea may lead to increased mixed layer (ML) warming or cooling relative to non‐BL conditions, depending on differences in ML properties and atmospheric forcing. We use 13 years of profiling float data from the Arabian Sea to identify when and where each impact is likely based on analysis of the ML temperature tendency. We use a novel method based on the vertical spice profile to identify BLs and their characteristics. BLs are most likely to increase warming during the northeast monsoon, owing to temperature inversions, preceding the development of the miniwarm pool and onset of the southwest monsoon. This effect is nonuniform and is counteracted in some regions by increased penetration of solar radiation below the shallower ML associated with BL. Relative rates of cooling increase in the presence of BL during the southwest monsoon; intermonsoon periods show little net effect from BL. Plain Language Summary: Barrier layers are frequently observed in the world's tropical and subtropical oceans in regions where salinity plays a more important role in determining changes to the upper ocean density than temperature. In the Arabian Sea, where the monsoons affect billions of lives, we wish to understand how the presence of barrier layers may affect the evolution of the upper ocean temperature and thus potentially the behavior of the monsoons. We find significant changes to the mixed layer properties that influence the evolution of sea surface temperature, sometimes leading to increased warming but also frequently leading to increased cooling. Key Points: Effect of barrier layers on sea surface temperature in the southeast Arabian Sea varies with season and is nonuniform Increased heating associated with barrier layers only significantly observed during northeast monsoon and in isolated patches Increased cooling associated with barrier layers during southwest monsoon due to shallower mixed layers increased penetrative radiation